2003
DOI: 10.1002/chem.200304917
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cystine Knots in Collagen Folding and Stability, Part I. Conformational Properties of (Pro‐Hyp‐Gly)5 and (Pro‐(4S)‐FPro‐Gly)5 Model Trimers with an Artificial Cystine Knot

Abstract: In analogy to the cystine knots present in natural collagens, a simplified disulfide cross-link was used to analyse the conformational effects of a C-terminal artificial cystine knot on the folding of collagenous peptides consisting of solely (Pro-Hyp-Gly) repeating units. Assembly of the alpha chains into a heterotrimer by previously applied regioselective disulfide-bridging strategies failed because of the high tendency of (Pro-Hyp-Gly)(5) peptides to self-associate and form homotrimers. Only when side-chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 62 publications
4
45
1
Order By: Relevance
“…[6] We demonstrate that the monomeric species have to prefold into the Figure 1. Sequence composition of the homotrimers I ± V whose syntheses were attempted or carried out in the present study; heterotrimer VI with the C-terminal artificial cystine knot [6] is reported for comparison.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…[6] We demonstrate that the monomeric species have to prefold into the Figure 1. Sequence composition of the homotrimers I ± V whose syntheses were attempted or carried out in the present study; heterotrimer VI with the C-terminal artificial cystine knot [6] is reported for comparison.…”
Section: Introductionmentioning
confidence: 71%
“…ESI-MS and, particularly, the isotope pattern of FT-ICR-MS confirmed the disulfide-cross-linked trimeric composition of the compounds as illustrated, for example, for trimer II, in Figure 2. Although even the NMR spectra were consistent with a single set of cystine connectiv- [6] for comparison. ities (see below), the unambiguous proof for the presence of a single cystine knot isomer can only be expected from X-ray crystallographic analysis.…”
Section: Synthesis Of the Trimersmentioning
confidence: 87%
See 2 more Smart Citations
“…29,31,[53][54][55] Modeling and molecular dynamics (MD) simulations served to optimally fit the cystine knot into the triple-helix without steric clashes, 29 a fact that was recently confirmed by NMR structural analysis of a model peptide containing such disulfide connectivities. 56 In view of the positive experiences with these disulfide-cross-linked collagenous heterotrimers and also because of the presence of a cystine knot downstream from the ␣1␤1 adhesion epitope, the two heterotrimers A and B ( Figure 2) were selected as possible mimics of the ␣1␤1 adhesion epitope of collagen type IV. 55 These trimers contain the sequence portions 457-468 of the aligned ␣1 and ␣2 chains of collagen type IV which encompass the residues 461 directly involved in binding to ␣1␤1 integrin.…”
Section: Design Of Cell-adhesive Collagen Type IV Mimeticamentioning
confidence: 99%